Exploring Individual Antecedents of Performance Error: False Starts in Collegiate Football. Issue 3 (27th May 2021) - Graczyk, Joseph Patrick; Dierdorff, Erich C.; Rubin, Robert S.; Lemmon, Grace
ABSTRACT: We explored antecedents of performance errors, where such errors are defined as unintended deviations from specified standards. The context of our examination was collegiate football, with participants that were position players on the offensive line. Performance errors were operationalized as false starts. Using data from archival sources and primary data collection, we explored the potential effects of several individual attributes that have been previously theorized as antecedents of performance errors. These attributes included perceptual-cognitive skill, general mental ability, personality traits, self-regulatory foci, and regulation of emotion. Significant effects were revealed across the various individual attributes leading to incidents of performance error. Implications for future research and practice on performance errors are discussed.